Individual factors increasing complexity of drug treatment: a narrative review - Schmidt, Steffen J.; Wurmbach, Viktoria; Lampert, Anette; Bernard, Simone; Haefeli, Walter E.; Seidling, Hanna; Thürmann, Petra A.; Wilm, Stefan; Mortsiefer, Achim; Altiner, Attila; Sparenberg, Lisa; Szecsenyi, Joachim; et al. (European journal of clinical pharmacology, 2020)
Complexity of drug treatment is known to be a risk factor for administration errors and nonadherence promoting higher healthcare costs, hospital admissions and increased mortality. Number of drugs and dose frequency are parameters often used to assess complexity related to the medication regimen. However, factors resulting from complex processes of care or arising from patient characteristics are only sporadically analyzed. Hence, the objective of this review is to give a comprehensive overview of relevant, patient-centered factors influencing complexity of drug treatment.